2014
DOI: 10.1111/jocn.12720
|View full text |Cite
|
Sign up to set email alerts
|

The support needs of new graduate nurses making the transition to rural nursing practice in Australia

Abstract: The study contributes new knowledge to the discussion of issues concerning support mechanisms for new graduate nurses as they make the transition to rural nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 27 publications
(74 reference statements)
3
68
0
Order By: Relevance
“…Thematic analysis revealed three major themes representing the new graduate's experience of support at each milestone of transition and these findings have been reported previously (Lea & Cruickshank ). The fourth major theme: The Rural RN's Experience with Newly Graduated Nurses in Rural Practice has three subthemes and this paper reports on one major subtheme: Providing support to newly graduated nurses .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Thematic analysis revealed three major themes representing the new graduate's experience of support at each milestone of transition and these findings have been reported previously (Lea & Cruickshank ). The fourth major theme: The Rural RN's Experience with Newly Graduated Nurses in Rural Practice has three subthemes and this paper reports on one major subtheme: Providing support to newly graduated nurses .…”
Section: Resultssupporting
confidence: 83%
“…Also it is not clear to graduates what staff expectations are with respect to exactly what aspects of workload and responsibility they are expected or have license to seek support with. In addition, as previously identified in an earlier paper (Lea & Cruickshank ) rural graduates are reluctant to approach RNs for support during a shift because they observed that the experienced RNs were often busy with their own workload.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Competence development as a process was a strong theme evident in the literature (Hengstberger‐Sims et al, ; Kumaran & Carney, ; Lea & Cruickshank, ; Lima, Newall, Jordan, Hamilton, & Kinney, ; Lima, Newall, Kinney, Jordan, & Hamilton, ; Olson, ; Pellico et al, ; Takase, Nakayoshi, & Teraoka, ; Wangensteen et al, ). Four of the quantitative studies used the Nurse Competence Scale (Meretoja, Isoaho, & Leino‐Kilpi, ) to assess competence between 4 and 10 months post registration (Hengstberger‐Sims et al, ; Lima et al, ; Lima et al, ; Wangensteen et al, ), demonstrating that at an early stage graduates have a lower self‐assessed competence than later in their transition year.…”
Section: Resultsmentioning
confidence: 99%
“…Being overwhelmed is an emotion that occurs when a person is faced with too much of anything; a prolonged experience of being overwhelmed increases the duration of transition shock. Lea and Cruickshank (, ) and Mellor and Greenhill () revealed that new graduate nurses felt overwhelmed and unprepared and less supported in comparison with metropolitan‐based nurses. Initially, new graduates did not realise that the role would be significantly different from that of a student nurse and consequently experienced a degree of transition shock within the first few weeks of commencing their programmes (Lea & Cruickshank, ).…”
Section: Resultsmentioning
confidence: 99%